(untitled) (Práxis Educativa, 2022)
This article is the result of a research that aimed to understand what the possibilities of the construction of ethnic-racial identity in the Primary and Secondary Teacher Training Courses. To this end, we dialogued with three women, black and schoolteachers, who graduated from a secular institution located in the city of Muzambinho, in the south of Minas Gerais, Brazil. Through their narratives, we sought to understand ruptures, possibilities and conquests of rights from the acquired training. Oral history was the main research approach. The following procedures were also used: analysis of photographs, consultation of school documentation in the institution’s collection, literature review. The results achieved indicate that black schoolteachers build their ethnic-racial identity in a silencing training environment that is ideologically oriented by values ​​based on whiteness. Keywords: Black teachers. Black identity. Institutional racism.